Desafios socioambientais decorrentes da implantação de reforma agrária sob mediação de educação ambiental - Leonardo, Josiane Bielski (2021)
In a country where socio-environmental inequalities and injustices stand out in all sectors of society, access through land could not be different, and like so many others, this is also a subject of discussion, conflicts, controversies, and political disputes. The implementation of Agrarian Reform and rural encampments can generate several impacts and social challenges to the community and biodiversity in its surroundings. This is just a reality that portrays the problems historically present in the agrarian issue in Brazil. In view of this fact, this study aimed to identify the possible socio-environmental impacts caused by the implementation of an Agrarian Reform camp and, under the mediation of Environmental Education, to propose actions to raise awareness in the community. The research was approved by the Research Ethics Committee and carried out in a rural Agrarian Reform camp located in the Southwest region of Paraná, occupied by members of the MST. The methodology used is a quanti-qualitative approach, where the tools for data collection are the interview with camped residents, the questionnaire with teachers from the traveling school and physical-chemical sampling to assess the quality of water and soil. From the information collected, it is possible to understand and list the main social and environmental challenges of the community that affect the living condition of the population's , such as: the quality of water is not suitable for human consumption; the soil suffers from the alterations caused by the Pinus monoculture carried out before the occupation; there is pollution from burning and incorrect disposal of waste due to the inexistence of garbage collection at the site; precariousness in education; lack of professional training; lack of essential school resources and subsidies; inefficiency of public policies; precariousness of basic sanitation; predominance of conventional agriculture and land leasing due to difficulties in accessing resources and techniques for implementing agroecology, among others. Environmental Education was a strong instrument for the community, proposing actions to minimize these challenges.